The coverage of the President succession issue by the Daily news and the Herald, prior and post the ZANU PF December 2014 Congress. - Teverah, Bellington (Midlands State University, 2017)
This dissertation seeks to explore, understand and critique the role played by the daily news and The Herald in their representation of factional and succession battles in ZANU PF. The period covered is prior and post the December 2014 ZANU PF elective congress. It is for the first time the factional battles in ZANU PF have been fought in the media. The study is qualitative in nature and it uses the Archival research method in the collection of data. Through content analysis and Critical Discourse Analysis (CDA) it was established that The Herald has been used as a tool to denigrate the Mujuru faction through character assassination and one sided reporting. The daily news however, sought to fight for the marginalised Mujuru faction by being a counter voice. Journalism ethical standards were however trampled upon by the two newspapers in their coverage of ZANU PF factional fights.